Analytical study on the implications of the GATS Agreement and its implications on the Egyptian banking sector - رشيد ثائر محمود; محمد ايهاب عباس (Journal of Economics and Administrative Sciences, 2019)
International trade in services is becoming increasingly important as it is an economic activity that deals with invisible trade, which has become increasingly important in the balance of international trade. The establishment of the WTO is a starting point in international trade relations. It is responsible for all aspects of international trade, , And in view of the continued increase in international trade in services, the need for more internationally recognized rules has become more urgent, especially as it has been increasingly proven that the traditional framework of public services is inadequate to operate some of the most dynamic and innovative sectors of the economy. (GATS) to be the regulatory framework for this sector. Despite the negative effects of the GATS on the banking sector in Egypt, especially with regard to the ability of local banks to face severe competition as they are still not ready due to the decline of their capital And the humbleness of the services it provides, there are a number of positive impacts that are identified and can contribute significantly to the maintenance of national interest.